The effect of hydro-alcoholic of Phoenix Dactylifera extract on sleep and EEG in rat - Sahar Rahimi; Hojjatollah Alaie; Parham Reisi; Zahra Siahmard; Behzad Zolfaghari; Aliasghar Pourshanazari (Mashhad University of Medical Sciences, 2017)
Objective: Hard envelope of date palm pollen is used as a sedative and calmative compounds in Iranian traditional medicine. We tried to study the effects of Phoenix dactylifera (Tarooneh) extract on sleep time and Brian waves. Materials and Methods: Rats were divided into control and test groups in sleep experiment. Control groups included intact group (without any injection), negative control group (saline) and positive control group (midazolam 0.1 mg/kg). Test groups received three doses of Tarooneh extract (62.5, 125 and 250 mg/kg). Rat were placed in sleep physiograph system and recording started 20 min after 2-hr calming down. Four parameters including sleep time, awakening, most activity period and main sleep time interval were measured. In EEG experiment electrodes were placed under the cranium for EEG recording and waves were compared with their baselines. Results: All doses of the extract increased sleeping time (p< 0.05) but just the dose of 250 mg/kg (p